(untitled) (Asian Business Research, 2021)
The Higher Education Institutions (HEIs) in Lebanon have been heavily impacted since the COVID-19 pandemic outbreak. The majority of the institutions had to react to the sudden decision to go online. In fact, they had to develop unplanned E-learning programs to assure the academic year‟s survival. In Lebanon, the Ministry of Education & Higher Education (MEHE) has ordered all educational institutions, public and private, to stop physical learning and start implementing E-learning through various online platforms. Because of Lebanon‟s unprepared infrastructure, students in universities struggled to continue their studies and to keep pace with others who have better situations. The purpose of this study is to assess the factors that may impact the success of E-learning in Lebanese universities and that affect students‟ satisfaction in adapting to this unplanned phase. The study is quantitative, explorative, descriptive and causal. A questionnaire was designed to collect primary data from 380 university students belonging to ten universities. Data analysis was carried out using the SPSS version 25 software. Several statistical techniques were performed including descriptive statistics and carrying out relational analysis via Factor Analysis (FA) and linear regression. Five constructs were defined namely, (1) Infrastructure, (2) Computer Skills, (3) E-Learning Content & Autonomy, (4) Support from others, and (5) Satisfaction. Results show that students‟ satisfaction is strongly influenced by the other four internal (2) and external (2) factors. Findings will support a set of recommendation directed to decision makers in HEI and the MEHE officials.